1995
DOI: 10.1007/bf00838491
|View full text |Cite
|
Sign up to set email alerts
|

Urinary angiotensin-converting enzyme activity in type 2 diabetes mellitus: its relationship to diabetic nephropathy

Abstract: Urinary angiotensin-converting enzyme (ACE) and urinary N-acetyl-beta-D-glucosaminidase (NAG) were measured after a 5-year interval in 38 non-azotemic type 2 diabetic patients. Of these patients at baseline, 16 had nil nephropathy, 15 had incipient nephropathy, and 7 had overt nephropathy. During the follow-up, 6 and 1 of the 16 patients with nil nephropathy developed incipient and overt nephropathy, respectively. Four of the 15 patients with incipient nephropathy progressed to overt nephropathy. The 7 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Nosadini 216 was not selected as no normoalbuminuric control group was included in the article. Miyauchi, 217 Wirta, 218 Friis and Pedersen 66 and Berrut 219 were also selected. Features of the seven selected studies are shown in Table 31.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nosadini 216 was not selected as no normoalbuminuric control group was included in the article. Miyauchi, 217 Wirta, 218 Friis and Pedersen 66 and Berrut 219 were also selected. Features of the seven selected studies are shown in Table 31.…”
Section: Search Resultsmentioning
confidence: 99%
“…Other articles selected were Nelson, 231 John, 90 Beatty, 63 Kawazu, 232 Chan, 61 Miyauchi, 217 Berrut, 219 Song, 233 Tanaka, 150 Nosadini 216 and de Grauw. 72 ( Table 32).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE expression is increased in renal glomeruli (34,51,69) and reduced in tubules of most DKD animal models (51,65,68,69), where ACE protein quantity correlates tightly with its enzymatic activity (65). In human DKD, however, ACE protein is increased in both glomerular and tubular compartments in kidney biopsies (17,30,33,41) and also increased in urine samples from people with DKD (6,15,32). We found increased urine ACE activity in streptozotocin-treated mice and, consistent with ACE overexpression in human kidney biopsies, we found higher urine ACE protein concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in urinary levels of NAG at follow‐up was reported in type 2 diabetic patients with nephropathy which was accentuated by the severity of the complication. There was no such increase in patients without nephropathy 158. Moreover, in the UK Prospective Diabetes Study (UKPDS), the occurrence of NAG‐uria among 672 newly diagnosed type 2 diabetic patients was much higher than that of albuminuria (66% and 28%, respectively) 66.…”
Section: Type 2 Diabetes and Markers Of Renal Impairmentmentioning
confidence: 98%